LATGALE INHABITANTS’ SATISFACTION WITH THE STATE IN CONTEXT OF THEIR FEELING OF HAPPINESS - Kalvāns, Ēriks (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The aim of this scientific research article is to describe the satisfaction with state of Latgale inhabitants’, as well as illustrate how this factor interacts with their feeling of happiness. A number of studies confirmed the link between happiness and the socio-economic conditions in the state. The low standard of living of Latgale’s inhabitants resulted in a fast decline of the number of inhabitants in the region. The unemployment rate in Latgale is the largest rate of unemployment in Latvia. Because of this problem of satisfaction with the state is very topical in this region. The theoretical interpretation of the happiness phenomenon is based on the findings of positive psychology, according to which happiness is defined as a life satisfaction and positive evaluation of his life and positive emotions over negative emotions. The author developed methodology „Family, Job, State” and "Oxford happiness questionnaire" adapted by the author to Latvian culture and socio-demographic survey, were used in the research paper. It was found out that Latgale inhabitants are not satisfied with the state socio-economic situation, state influence on personality, also the emotional attitude towards the state is at a low level.